2018
DOI: 10.1007/s00227-018-3418-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid signatures connect thiamine deficiency with the diet of the Atlantic salmon (Salmo salar) feeding in the Baltic Sea

Abstract: Thiamine (vitamin B1) deficiency in salmonids related to a lipid-rich fish diet causes offspring mortality in the yolk-sac fry phase. A low free thiamine (THIAM) concentration in eggs is an indication of this syndrome. Thiamine deficiency of salmon (Salmo salar) feeding in the Baltic Sea, called M74, was connected to the principal prey fish and feeding area using fatty acid (FA) signature analysis. The FAs of feeding salmon from two areas of the Baltic Sea, the Baltic Proper (57°10′ 19°30′) and the Bothnian Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(76 citation statements)
references
References 52 publications
1
72
3
Order By: Relevance
“…The second hypothesis is that M74 arise when salmon eat proportionally more smallsized sprat compared to large sprat and herring [7,26]. The small sized sprat have relatively low concentrations of thiamin per energy content compared to other clupeids [6,9,27]. Yet another hypothesis is that the prey fish of salmon (sprat and herring) contain a thiamin degrading enzyme called thiaminase reducing the uptake of thiamin [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The second hypothesis is that M74 arise when salmon eat proportionally more smallsized sprat compared to large sprat and herring [7,26]. The small sized sprat have relatively low concentrations of thiamin per energy content compared to other clupeids [6,9,27]. Yet another hypothesis is that the prey fish of salmon (sprat and herring) contain a thiamin degrading enzyme called thiaminase reducing the uptake of thiamin [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the changes in abiotic conditions and consequent changes in the species composition and size distribution of primary producers, that have occurred in the Baltic Sea, could have constrained the flow of thiamin from lower to higher trophic levels of the system. However, not only bottom-up factors such as nutrients seem to play a role since it has also been shown that M74 incidence is correlated with the stock size of sprat [7,26], with the suggested cause of M74 being salmon consumption of small individuals with a relatively low thiamin concentration per unit of fat content [6,27]. Our data supports that M74 is most severe during periods with high abundance of planktivorous fish but correlations occur, not only for sprat, but also for herring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations